Spin echo magnetic resonance imaging. Issue 4 (22nd March 2013) - Jung, Bernd André; Weigel, Matthias
Abstract The spin echo sequence is a fundamental pulse sequence in MRI. Many of today's applications in routine clinical use are based on this elementary sequence. In this review article, the principles of the spin echo formation are demonstrated on which the generation of the fundamental image contrasts T1, T2, and proton density is based. The basic imaging parameters repetition time (TR) and echo time (TE) and their influence on the image contrast are explained. Important properties such as the behavior in multi‐slice imaging or in the presence of flow are depicted and the basic differences with gradient echo imaging are illustrated. The characteristics of the spin echo sequence for different magnetic field strengths with respect to clinical applications are discussed. J. Magn. Reson. Imaging 2013;37:805–817. © 2013 Wiley Periodicals, Inc.